2011
DOI: 10.1016/j.brainres.2011.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of oxidative stress and inflammation to anxiety and hypertension

Abstract: Previously, we have published that pharmacological induction of oxidative stress causes anxiety-like behavior in rats and also is associated with hypertension in these animals. Here, we report that sub-chronic induction of oxidative stress via pharmacological induction leads to i) reduction in glyoxalase (GLO)-1 and glutathione reductase (GSR)-1 expression; ii) calpain mediated reduction of brain derived neurotrophic factor (BDNF) levels; iii) NFκB mediated upregulation of proinflammatory factors interleukin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 59 publications
4
76
0
1
Order By: Relevance
“…Furthermore, although research into the effects of centrally and peripherally administered TNF-a blockade on cognition and depressive symptoms has improved our understanding of cytokine actions in the CNS (Couch et al, 2013;Tobinick and Gross, 2008), little work has been undertaken to enhance our knowledge on the effects of TNF-a blockade on anxiety behaviors. This is surprising as peripheral inflammatory conditions, such as RA and psoriasis, involving TNF-a upregulation are commonly associated with anxiety Salim et al, 2011), although the exact mechanisms whereby inflammation induces psychiatric symptoms are unclear (Chandarana et al, 1987;Couch et al, 2013). It is suggested that peripheral inflammation can cause upregulation of TNF-a, which in turn activates macrophages peripherally and microglia centrally (Qin et al, 2007) and is further linked to the development of anxiety-like behavior (Wohleb et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although research into the effects of centrally and peripherally administered TNF-a blockade on cognition and depressive symptoms has improved our understanding of cytokine actions in the CNS (Couch et al, 2013;Tobinick and Gross, 2008), little work has been undertaken to enhance our knowledge on the effects of TNF-a blockade on anxiety behaviors. This is surprising as peripheral inflammatory conditions, such as RA and psoriasis, involving TNF-a upregulation are commonly associated with anxiety Salim et al, 2011), although the exact mechanisms whereby inflammation induces psychiatric symptoms are unclear (Chandarana et al, 1987;Couch et al, 2013). It is suggested that peripheral inflammation can cause upregulation of TNF-a, which in turn activates macrophages peripherally and microglia centrally (Qin et al, 2007) and is further linked to the development of anxiety-like behavior (Wohleb et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate excitotoxicity has been highlighted as having an important role in the pathology of mood disorders, including anxiety and depression [2,42,59]. In addition, the importance of the NMDA receptor and its subunits NR1, NR2A-D and NR3, which are coded by different genes [58], have been reported in many basic and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Over a decade ago, elevated levels of complement component (C)4, IL-6 and CRP, but not C3, were found to be associated with depression [42]. Oxidative stress induced by administration of L-buthionine-(S, R)-sulfoximine (BSO) [43] and xanthine plus xanthine oxidase (X+XO) [44] promotes NF-κB-dependent inflammation [45] and causes anxiety-like behaviour in rats.…”
Section: Inflammation and Oxidative Stressmentioning
confidence: 99%